2019
DOI: 10.1002/adfm.201900809
|View full text |Cite|
|
Sign up to set email alerts
|

Direct Ink Writing of Adjustable Electrochemical Energy Storage Device with High Gravimetric Energy Densities

Abstract: 3D printing graphene aerogel with periodic microlattices has great prospects for various practical applications due to their low density, large surface area, high porosity, excellent electrical conductivity, good elasticity, and designed lattice structures. However, the low specific capacitance limits their development in energy storage fields due to the stacking of graphene. Therefore, constructing a graphene‐based 2D materials hybridization aerogel that consists of the pseduocapacitive substance and graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 37 publications
3
75
1
Order By: Relevance
“…Direct ink writing (DIW) is one of the most commonly used 3D‐printing techniques. It offers great flexibility in the material (ink) selection and has been recently applied to prepare electrodes for electrochemical energy storage devices, including lithium‐ion batteries, sodium‐ion batteries, lithium–sulfur batteries, lithium metal batteries, and supercapacitors . In comparison to bulk electrodes, these 3D‐printed electrodes have shown improved electrolyte infiltration and ion diffusion …”
Section: Methodsmentioning
confidence: 99%
“…Direct ink writing (DIW) is one of the most commonly used 3D‐printing techniques. It offers great flexibility in the material (ink) selection and has been recently applied to prepare electrodes for electrochemical energy storage devices, including lithium‐ion batteries, sodium‐ion batteries, lithium–sulfur batteries, lithium metal batteries, and supercapacitors . In comparison to bulk electrodes, these 3D‐printed electrodes have shown improved electrolyte infiltration and ion diffusion …”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the voltage can be maximized by matching two electrodes with distinct voltage windows in an asymmetric cell configuration, further augmenting the energy density [16,17]. Pioneer studies have demonstrated that asymmetric supercapacitor (ASC) devices can be constructed by 3D printing of rGO-supported hybrid inks (e.g., VO x /rGO//VN/rGO [18], G/ZnV 2 O 6 @Co 3 V 2 O 8 //G/VN [19]), readily harvesting favorable gravimetric and areal energy densities. Nevertheless, the lightweight feature of carbon-based electrodes greatly compromises the volumetric energy density of energy storage systems toward practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several reports on 3D‐printed supercapacitors have been published based on GO and its composites because of their large surface area, high electrical conductivity, good processability and tunable structure. [ 50,51,58 ]…”
Section: D Material‐based 3d Printing For Energy‐related Applicationsmentioning
confidence: 99%
“…Adding a 2D pseudocapacitive additive to the GO to form a mixed 3D aerogel can solve the problem of aggregation and restacking of these active materials, thus achieving higher capacitance and charge retention. Zhao et al [ 58 ] investigated a hybrid aerogel microlattice with a graphene/ZnV 2 O 6 @Co 3 V 2 O 8 2D sheet‐like structure and a graphene/VN 2D sheet‐like structure, respectively serving as the cathode and anode. The composite inks were first prepared by mixing a concentrated GO solution with the other precursors such as ZnV 2 O 6 @Co 3 V 2 O 8 , Co 3 V 2 O 8 or VN and were used to prepare a 3D electrode by a home‐made extrusion 3D printing machine.…”
Section: D Material‐based 3d Printing For Energy‐related Applicationsmentioning
confidence: 99%